2023
DOI: 10.3390/cancers16010032
|View full text |Cite
|
Sign up to set email alerts
|

Role of c-Src in Carcinogenesis and Drug Resistance

Lukmon Raji,
Angelina Tetteh,
A. R. M. Ruhul Amin

Abstract: The aberrant transformation of normal cells into cancer cells, known as carcinogenesis, is a complex process involving numerous genetic and molecular alterations in response to innate and environmental stimuli. The Src family kinases (SFK) are key components of signaling pathways implicated in carcinogenesis, with c-Src and its oncogenic counterpart v-Src often playing a significant role. The discovery of c-Src represents a compelling narrative highlighting groundbreaking discoveries and valuable insights into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 179 publications
0
4
0
Order By: Relevance
“…In each PPI network, SRC, GAPDH, TNF, and AKT1 were among the top five highest-degree targets. SRC is associated with increased tumor progression, invasion, and metastasis in many cancers ( 74 , 75 ). TNF plays a crucial role in cancer treatment and autoimmunity ( 76 , 77 ), while AKT1 is linked to breast cancer and ovarian cancer ( 78 , 79 ).…”
Section: Resultsmentioning
confidence: 99%
“…In each PPI network, SRC, GAPDH, TNF, and AKT1 were among the top five highest-degree targets. SRC is associated with increased tumor progression, invasion, and metastasis in many cancers ( 74 , 75 ). TNF plays a crucial role in cancer treatment and autoimmunity ( 76 , 77 ), while AKT1 is linked to breast cancer and ovarian cancer ( 78 , 79 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that at the molecular level, PTPRE dephosphorylates and thereby activates SRC [9,19,20]. Activation of SRC has been shown to activate downstream pathways like, e.g., the PI3K-AKT pathway, playing an essential role in cell proliferation, survival, growth, tumor initiation, metastasis, and drug resistance (for review see: [26]). The activity of SRC is significantly reduced in tumor cells lacking PTPRE and restoring SRC activity revealed that it is only its reduced activity that caused aberrant proliferation rates of tumor cells lacking PTPRE [9].…”
Section: Discussionmentioning
confidence: 99%
“…PTPRE regulates phosphorylation processes with the involvement of different other kinases like SRC [10,20], ERK1/2 [23], glucocorticoid kinase 3 (SGK3) and AKT downstream signaling [24,25]. As all of the above-mentioned signaling molecules mediate effects related to cell proliferation, growth, viability, tumor initiation and tumor cell migration [26][27][28], effects likewise seen to be influenced following PTPRE silencing, we investigated ERK/p-ERK, SRC/pSRC, AKT/p-AKT, and SGK3/pSGK3 expression after PTPRE knockdown in order to reveal possible PTPRE downstream signaling mechanisms in etoposide-resistant RB cells.…”
Section: Ptpre Downstream Signalingmentioning
confidence: 99%
“…Consequently, numerous researchers are focused on identifying novel molecular biomarkers that could predict treatment responses and prevent tumor relapse. It has been reported that Src family kinases (SFKs) play a role in advancing oncogenesis and in conferring resistance to chemotherapy drugs as well as to molecular targeted therapies [2].…”
Section: Introductionmentioning
confidence: 99%